Hey sorry the equation is a little different than that…
(ex)x·e4x + 4 = 1
all the xs and 4x+4 are all exponents.
(ex)x·e4x + 4 = 1… so i need to solve for x…. how the hell do I do that???
2 answers
If you mean e^x * e^(4x+4) = 1
just take log of both sides:
x + (4x+4) = 0
5x = -4
x = -4/5
check
e^(-4/5) * e^(-16/5 + 20/5) = e^(-4/5) * e^(4/5) = e^(-4/5 + 4/5) = e^0 = 1
just take log of both sides:
x + (4x+4) = 0
5x = -4
x = -4/5
check
e^(-4/5) * e^(-16/5 + 20/5) = e^(-4/5) * e^(4/5) = e^(-4/5 + 4/5) = e^0 = 1